Flowers Against Biography: Translating Sylvia Plath's Botanical Imagery in Amelia Rosselli's Poetics. - Binetti, Roberto (Forum for Modern Language Studies, 2025)
This article explores the influence of Sylvia Plath's botanical imagery on Amelia Rosselli's poetics, focusing on how Rosselli's 1970s translations of Plath intersected with her own evolving poetic language. Moving beyond biographical readings, the study examines how both poets use flowers and plants as symbols of psychological turmoil, subverting traditional associations with femininity and beauty. Rosselli transforms Plath's floral motifs in Documento (1966–1973) (1976), turning them into a tool for exploring the fragmentation of the lyric subject and forging a poetics of objectivity. By reading together Plath's 'Black Rook in Rainy Weather' and Rosselli's 'I fiori vengono in dono e poi si dilatano', the article reveals their shared concerns with poetic creation, vitality and decay. It argues that Rosselli's translation practice exemplifies this poetics of objectivity, preserving Plath's foreignness and resisting assimilation into the Italian literary canon. This approach reimagines nature, subjectivity and poetic creation across linguistic and cultural boundaries.